CUSTOMER RETENTION STRATEGIES FOR GENERATION C (Third Sector Social Economic Review, 2017)
After the technological developments, the digital age started, and one of the main results of it is the increase of computer usage and interaction between consumers. The new age and rising popularity of social media have revealed the connected consumers which can be called as a Generation C that is described as a Social Media Generation. These consumers can connect with each other and share their experiences about product and services. Gen C’s consumption behavior can be shaped by social media that is the core factor of connection between consumers.  Nowadays, because of the using social media, the traditional promotion strategies could not be successful as much as last century. In this paper, digital age, social media, the concept of Gen C are discussed. The aim of this paper is to reveal a conceptual discussion the influence of Generation C on the companies’ promotion strategies. This paper will be useful for marketing researchers towards comprehensive presenting of the new generation.
Keywords: Digital Age; Generation C; Customer; Promotion; Promotion Strategies